The impact of bioinsecticide overdoses of Beauveria bassiana on species diversity and abundance of not targeted arthropods in South Sumatra (Indonesia) freshwater swamp paddy - KHOIRUL IKHSANUDIN HANIF; Siti Herlinda; CHANDRA IRSAN; YULIA PUJIASTUTI; GHANNI PRABAWATI; HASBI; TILI KARENINA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hanif KI, Herlinda S, Irsan C, Pujiastuti Y, Prabawati G, Hasbi, Karenina T. 2020. The impact of bioinsecticide overdoses of Beauveria bassiana on species diversity and abundance of not targeted arthropods in South Sumatra (Indonesia) freshwater swamp paddy. Biodiversitas 21: 2124-2136. Bioinsecticides have been shown to reduce insect pest populations, but it is necessary to monitor the effect of bioinsecticide overdoses on non-target arthropods because they are abundant in rice fields. This study aimed to analyze the impact of bioinsecticide overdoses of B. bassiana on species diversity and abundance of non-target arthropods. Bioinsecticides derived from Beauveria bassiana were sprayed on the paddy every two weeks until the ripening stage, at a dose of 1, 2, 3, 4 L.ha-1, control (without insecticide), and abamectin as prescribed. The abundance of spiders and predatory arthropods did not decrease when bioinsecticides were applied but the abundance of spiders, especially Lycosidae and Salticidae dropped significantly when abamectin was applied. The abundance of the parasitoid decreased significantly when abamectin was applied, but the abundance of parasitoids applied by bioinsecticide was not significantly different from those of control. The abundance of insect pests started to decrease when bioinsecticide was applied to 2, 3 or 4 L.ha-1. The diversity species of non-target arthropods (spiders, predatory arthropods, and parasitoids) tended to decrease when it was applied bioinsecticides 3 and 4 L.ha-1 or abamectin, but their abundance remained high and no species dominance was found. For this reason, the correct dosage for suppressing insect pests abundance by not decreasing the abundance and diversity of non-target species is 2 L.ha-1 and applied when herbivore abundance is high.